2017
DOI: 10.1007/s12105-017-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Associated Cancers of the Head and Neck: An Australian Perspective

Abstract: Human papillomavirus (HPV) associated head and neck squamous cell carcinomas (HNSCCs), have become a serious global health problem. Despite decreases in HPV-negative HNSCCs, the prevalence of HPV-positive HNSCCs has significantly increased. HPV-positive cancers are associated with superior survival outcomes when compared to HPV-negative cancers, which appears likely to be associated with differences in the molecular pathogenesis of the two diseases. While therapies are still problematic, the current HPV vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the HPV-16 type accounts for approximately 90% of HPV-positive oropharyngeal cancers (OPCs) [10,11]. Epidemiological data showed that the incidence of HPV-related head and neck cancer (HNC) is increasing [12][13][14][15]. HPV-associated head and neck cancers have different risk factors, clinical characteristics, and tumor biology when compared to tobacco/alcoholassociated head and neck cancers [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the HPV-16 type accounts for approximately 90% of HPV-positive oropharyngeal cancers (OPCs) [10,11]. Epidemiological data showed that the incidence of HPV-related head and neck cancer (HNC) is increasing [12][13][14][15]. HPV-associated head and neck cancers have different risk factors, clinical characteristics, and tumor biology when compared to tobacco/alcoholassociated head and neck cancers [16].…”
Section: Introductionmentioning
confidence: 99%
“…HPV-associated head and neck cancers are characterized by a younger age at onset, basaloid/warty histopathology, as well as superior survival outcomes when compared with their HPV-negative counterparts [18]. HPV-associated malignancies of the head and neck arise mainly in oropharyngeal sites, such as tonsils, the base of the tongue, and oropharynx; other oral sites, such as the ventrolateral tongue, gingivae, cheek, palate, and floor of the mouth are mainly attributed to tobacco use and alcohol consumption [15,19].…”
Section: Introductionmentioning
confidence: 99%
“…Squamous Cell Carcinoma is the most commonly occurring cancer in oral cavity, which originates predominantly from buccal mucosa and tongue [1]. In Pakistan the burden of OSCC accounts for 10% of all cancers affecting both genders.…”
Section: Introductionmentioning
confidence: 99%
“…HPV-related oropharyngeal SCC are still diagnosed at lesser rates than HPV-negative OSCC and the prevalence of high-risk HPV positivity in OSCC varies widely between developing countries [1]. In the HPV-negative subsets, chronic exposures to carcinogens and extensive consumption of alcohol have been largely associated with the induction of neoplasms [1,[15][16][17]. Oral leukoplakia and oral lichen planus are among the most frequent oral potentially malignant lesions and patients with those lesions are more susceptible to developing OSCC [18][19][20][21].…”
Section: Introduction Oral Squamous Cell Carcinomamentioning
confidence: 99%